Cytotoxicity and chromosomal aberrations induced by acrylamide in V79 cells - Oliveira, Nuno G. (2015)
Acrylamide (AA) is a suspected human carcinogen found to be generated during the heating of carbohydrate-rich foodstuffs. AA exhibits 'Michael-type' reactivity towards reduced glutathione (GSH), resulting in vivo in the urinary excretion of mercapturic acid conjugates. GSH is a key factor for mammalian cell homeostasis, with diverse functions that include, among others, the Conjugation of electrophilic compounds and the detoxification of products generated by oxidative stress. Therefore, Studies focusing on the modulation of GSH are of great importance for the understanding of the mechanisms of AA-induced toxicity. This report addresses this issue by analyzing cytotoxicity (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) reduction assay) and clastogenicity (chromosomal aberrations) as endpoints in V79 cells after exposure to AA. The experiments described herein include the evaluation of the effect of buthionine sulfoximine (BSO), an effective inhibitor of GSH synthesis, GSH-monoethyl ester (GSH-EE), a compound that is taken up by cells and intracellularly hydrolysed to GSH, and also GSH exogenously added to culture medium. Pre-treatment with BSO increased the cytotoxicity and the frequency of aberrant cells excluding gaps (ACEG) induced by AA. While pre-treatment with GSH-EE did not modify the cytotoxicity or the frequency of ACEG induced by AA, co-treatment with AA and GSH decreased both parameters, rendering the cells less prone to the toxic effects of AA. In vitro studies in a cell-free system, using monochlorobimane (MCB), a fluorescent probe for GSH. were also performed in order to evaluate the role of AA in GSH depletion. The results show that spontaneous conjugation of AA with GSH in the extracellular medium is involved in the protection given by GSH. In Summary, these results reinforce the role of GSH in the modulation of the cytotoxic and clastogenic effects induced by AA, which may be relevant in an in vivo exposure scenario. (C) 2009 Elsevier B.V. All rights reserved.. - Fundacao para a Ciencia e a Tecnologia (FCT) [SFRH/BD/22612/2005, SFRH/BD/28773/2006]; Fundacao Calouste Gulbenkian [69405, 76438]. - The PhD grants to M.P. (SFRH/BD/22612/2005) and A.S.F (SFRH/BD/28773/2006) from Fundacao para a Ciencia e a Tecnologia (FCT) are acknowledged. We also acknowledge Fundacao Calouste Gulbenkian financial support (Grants 69405 and 76438).